2000
DOI: 10.1097/00004836-200012000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Hepatocellular Carcinoma

Abstract: The purpose of this study was to determine whether a relation does exist between clinicopathologic features and the prognosis of hepatocellular carcinoma (HCC) with respect to serum alpha-fetoprotein (AFP) levels at diagnosis. We reviewed the clinical data of 309 pathologically proven HCC cases divided into three groups: group 1 with normal AFP (<20 IU/mL), group 2 with moderately elevated AFP (20-399 IU/mL) and group 3 with markedly elevated AFP (> or =400 IU/mL). Of these, there were 76 (24.6%), 78 (25.2%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
202
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 43 publications
20
202
3
1
Order By: Relevance
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…10 These pathological and clinical features could be explained by a common protein network with AFP expression. Taking annexin A1 as an example, this protein is a major substrate for tyrosine kinases such as epidermal growth factor receptor and serine/threonine kinases such as protein kinase C 43,44 and has been implicated in cellular signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…9 Serum AFP alone has a limited role in the early diagnosis of HCC, because a considerable proportion of HCC patients do not have elevated serum AFP, and serum AFP can increase in patients with diseases other than HCC; it may, however, be a useful prognostic indicator, because the median survival rate of HCC patients with markedly elevated AFP was significantly shorter than that of patients with normal or moderately elevated AFP. 10 AFP is a multifunctional glycoprotein belonging to the family of albumin-like proteins. 11 AFP has been shown to serve as a dual regulator of growth in a multitude of cell types and cancers involving several mechanisms, including apoptotic regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In fact, the well-known UICC and AJCC staging (TNM) criteria do not define the relative prognostic weight of variables, in terms of residual liver function. 5 Although several studies have examined predictive factors for prognosis in relation to treatment, 1,[6][7][8][9][10][11][12][13][14][15][16] most of these have been performed in Asian institutions. Accordingly, these facilities and patient populations possess early detection plans, risk factors for primary liver cancer, a high proportion of expanding tumors, and differing rates of resectability, respectively, with regard to those in Western countries.…”
mentioning
confidence: 99%